Orbital angular momentum states of light : propagation through atmospheric turbulence - Khare, Kedar; Lochab, Priyanka; Senthilkumaran, Paramasivam (IOP series in advances in optics, photonics and optoelectronics., 2020)
Orbital Angular Momentum States of Light provides an in-depth introduction to modelling of long-range propagation of orbital angular momentum (OAM) modes as well as more general structured light beams through atmospheric turbulence. Starting with angular spectrum method for diffraction and description of structured light states, the book discusses the technical details related to wave propagation through atmospheric turbulence. The review of historical as well as more recent ideas in this topical area, along with computer simulation codes, makes this book a useful reference to researchers and optical engineers interested in developing and testing of free-space applications of OAM states of light. Part of IOP Series in Advances in Optics, Photonics and Optoelectronics.